High Dose Radiotherapy to Automated Implantable Cardioverter-Defibrillator: A Case Report and Review of the Literature. (7th September 2014) - Ahmed, Inaya; Zou, Wei; Jabbour, Salma K.
Abstract : We report a case of successful full-dose chemoradiotherapy to stage IIIB nonsmall cell lung cancer (NSCLC) in a 59-year-old man with extensive cardiac history and an automated implantable cardioverter-defibrillator (AICD) located within the radiotherapeutic field. In this case, the AICD was a St. Jude Medical Fortify Assura VR 1257-40Q ICD, and it was implanted prophylactically during bypass grafting. Although we do not recommend routine radiotherapy dose to exceed recommended current guidelines due to the potential risks to the patient, this is a situation where relocation of the device was not possible. Fortunately, our patient was not AICD-dependent; so following much discussion and deliberation, the decision was made to treat the patient with AICD in place. The patient completed definitive chemoradiotherapy with concurrent cisplatin and etoposide and thoracic irradiation to 69.6 Gy. The minimum, maximum, and mean doses to the AICD directly were 13.5 Gy, 52.4 Gy, and 29.3 Gy, respectively. The device withstood full thoracic radiation dose, and the patient denied cardiac symptoms during the time before, during, and after completion of therapy. We sought to offer this case for both teaching and guidance in practice and to contribute to the published literature currently available in this area.